2018
DOI: 10.3892/ol.2018.8004
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor PAQR3 associated with the clinical significance and prognosis in esophageal squamous cell carcinoma

Abstract: Progestin and adipoQ receptor family member 3 (PAQR3) is a novel tumor suppressor; however, its function in esophageal cancer is not well understood. The present study explored the association between PAQR3, and the survival and clinical phenotype in patients with esophageal squamous cell carcinoma (ESCC). The expression of PAQR3 in 80 cases of ESCC and its corresponding adjacent tissues was detected by reverse transcription-quantitative polymerase chain reaction. The results demonstrated that PAQR3 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…[418] However, others found that there were no relationships between tumor length and oncological outcomes in EC patients. [1923] Therefore, the prognostic significance of tumor length remains controversial. Because an individual study is likely to provide a biased result that may partly result from the small sample size, we conducted a systematic review and quantitative meta-analysis to comprehensively assess the prognostic significance of tumor length in EC patients.…”
Section: Introductionmentioning
confidence: 99%
“…[418] However, others found that there were no relationships between tumor length and oncological outcomes in EC patients. [1923] Therefore, the prognostic significance of tumor length remains controversial. Because an individual study is likely to provide a biased result that may partly result from the small sample size, we conducted a systematic review and quantitative meta-analysis to comprehensively assess the prognostic significance of tumor length in EC patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expression of PAQR3 in esophageal cancer tissues is lower than that in normal esophageal tissues, and is significantly correlated with tumor size, lymph node metastasis, and local recurrence among esophageal cancer patients. In addition, it inhibits the proliferation, cell cycle, clone formation, migration, and invasion of esophageal cancer cells, as confirmed in a nude mouse xenograft model ( Zhou et al, 2017 ; Bai et al, 2017 , 2018 ). In addition, PAQR3 expression is decreased in some other tumors such as osteosarcoma, gastric cancer, and breast cancer, and the functions in these tumor tissues are consistent with those mentioned above, and include the inhibition of the growth and migration of tumor cells ( Ling et al, 2014 ; Li et al, 2015 ; Ma et al, 2015 ; Zhao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 71%
“…The level of PAQR3 was decreased both in tissues and cells of esophageal cancer, and overexpression of PAQR3 significantly inhibited the proliferation, clone formation, and invasion of esophageal cancer cells and blocked the transition from the G1 phase to the S phase. Moreover, increased PAQR3 expression inhibited the growth of ECA-109 cell xenograft tumors ( Zhou et al, 2017 ; Bai et al, 2017 , 2018 ). Compared with adjacent tissues, the expression of PAQR3 in laryngeal squamous cell carcinoma (LSCC) tissues was significantly downregulated, and overexpression of PAQR3 inhibited the proliferation and invasion of LSCC cells ( Wu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, overexpression of PAQR3 suppressed the ERK pathway. 43,44 And, it was found that PAQR3 is lowly expressed in human ESCC cell lines. PAQR3 overexpression was shown to reduce malignant potential in cultured ESCC cells and attenuated the growth of xenografted tumors.…”
Section: Esophageal Squamous Cell Carcinoma Cellsmentioning
confidence: 99%
“…45 Jointly, the above findings demonstrated PAQR3 overexpression suppresses the aggressive phenotype of ESCC cells in culture and animals, indicating PAQR3 could be targeted for ESCC treatment. [43][44][45] Gastric cancer…”
Section: Esophageal Squamous Cell Carcinoma Cellsmentioning
confidence: 99%